The effect of carbon nanotubes and silica fume on compressive strength and flexural strength of cement mortars - Chaipanich A. (2017)
© 2017 Elsevier Ltd. All rights reserved. This paper reports the effect of carbon nanotubes on compressive strength and flexural strength of Portland cement- silica fume-carbon nanotubes cement mortars. Silica fume, by-product from silicon metal and ferro-silicon alloys industries was used as a cement replacement material at 10 % by weight. Carbon nanotubes, produced by CVD method was used as an additional material up to 1 % by weight. Water to binder ratio (w/b) of 0.5 was used for all mortar mixes. Samples were cured in water until being tested at the age of 28 days. The results show that the mortar with silica fume has higher compressive strength and flexural strength than Portland cement control and when used in combination with carbon nanotubes a further increase in compressive strength and flexural strength were observed with the optimum strengths obtained at 0.5% CNTs.